2018 Vegetable Production Handbook Chapter 10: Minor Vegetable Crop Production - Christian F. Miller; Qingren Wang; Ramdas Kanissery; Eugene J. McAvoy; Monica Ozores-Hampton; Richard N. Raid; Crystal A. Snodgrass; Julien Beuzelin; Dakshina R. Seal; Alicia J. Whidden; Shouan Zhang (EDIS)
This 34-page fact sheet is chapter 10 of the 2018 Vegetable Production Handbook. Written by Christian F. Miller, Qingren Wang, Ramdas Kanissery, Eugene J. McAvoy, Monica Ozores-Hampton, Richard N. Raid, Crystal A. Snodgrass, Julien Beuzelin, Dakshina R. Seal, Alicia J. Whidden, and Shouan Zhang, and published by the Horticultural Sciences Department, 2018.